Naturalizing sensemaking - Snowden, Dave (Informed by Knowledge: Expert Performance in Complex Situations, 2010)
The focus of this book is on how experts adapt to complexity, synthesi ze and interpret information in context, and transform or "fuse" dispa rate items of information into coherent knowledge. The chapters examin e these processes across experts (e.g. global leaders, individuals in extreme environments, managers, police officers, pilots, commanders, d octors, inventors), across contexts (e.g. space and space analogs, cor porate organizations, command and control, crisis and crowd management , air traffic control, the operating room, product development), and f or both individual and team performance. Successful information integr ation is a key factor in the success of diverse endeavors, including t eam attempts to climb Mt. Everest, crowd control in the Middle East, a nd remote drilling operations. This volume is divided into four sectio ns, each with a specific focus on an area of expert performance, resul ting in a text that covers a wide range of useful information. These s ections present well-researched discussions, such as: the management o f complex situations in various fields and decision contexts; technolo gical and training approaches to facilitate knowledge management by in dividual experts and expert teams; new or neglected perspectives in ex pert decision making; and the importance of ‘modeling’ expert performa nce through techniques and frameworks such as Cognitive Task Analysis, computational architectures based on the notion of causal belief mapp ing such as ‘Convince Me,’ or the data/frame model of sensemaking. The volume provides essential reading for researchers and practitioners o f Naturalistic Decision Making and those who study Expertise; Organiza tional and Cognitive Psychologists; and researchers and students in Bu siness and Engineering.